Traditional Chinese medicine Tongxie Yaofang treating irritable bowel syndrome with diarrhea and type 2 diabetes mellitus in rats with liver-depression and spleen-deficiency: A preliminary study - Xu, Weidong; Zhang, Zhiyi; Lu, Ye; Li, Mengxi; Li, Jiayao; Tao, Wenhua (Frontiers in Nutrition, 2022)
Tongxie Yaofang (TXYF), a Traditional Chinese Medicine with four components as follows: Rhizoma Atractylodis Macrocephalae (baizhu), Radix Paeoniae Alba (baishao), Pericarpium Citri Reticulatae (chenpi) and Radix Saposhnikovia Divaricata (fangfeng), benefits irritable bowel syndrome (IBS). Nonetheless, proofs of this formula ameliorating D-IBS and T2DM are required. This research aimed at investigating the efficacy of TXYF in treating inflammation in rats with D-IBS and T2DM using animal models. In this study, gavage with high-fat diet, fasciculation and senna was given to develop rat models with target diseases. To determine intestinal inflammations, major inflammatory factors, and intestinal permeability proteins, H&E staining, ELISA, and immunohistochemistry methods were employed, respectively. This study also utilized Western blot to discover potential inflammatory targets. Results of this research illustrates that TXYF treatment reduced the level of TNF-α, IL-1β and IL-6, and raised the IL-10 concentration in liver-depressed spleendeficient rats with D-IBS and T2DM, indicating controlled inflammatory reactions. Staining analysis also showed improved disease states of animal models. Furthermore, efficient rebounds of claudin-1, an intestinal permeability-associated protein, were detected. Moreover, TXYF may treat D-IBS and T2DM in rats via the rage pathway.